2017
DOI: 10.1002/14651858.cd009197.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal therapy for the management of cardiovascular disease in patients with chronic periodontitis

Abstract: Periodontal therapy for the management of cardiovascular disease in patients with chronic periodontitis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 95 publications
1
47
0
6
Order By: Relevance
“…Thus, there is insufficient evidence to support or refute the potential benefit of the treatment of periodontitis in preventing or delaying ACVD events [61]. Table 1 summarizes the evidence on the effect of periodontal therapy on surrogate markers of CVD.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Thus, there is insufficient evidence to support or refute the potential benefit of the treatment of periodontitis in preventing or delaying ACVD events [61]. Table 1 summarizes the evidence on the effect of periodontal therapy on surrogate markers of CVD.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…39 A meta-analysis of observational studies including 22 observational studies including 129,630 participants showed that patients with periodontitis have an increased risk of MI (OR 2.02, 95% CI 1.59-2.57). 40 A systematic review to investigate the effects of periodontal therapy in preventing the occurrence of, and management or recurrence of, CVD in patients with chronic periodontitis 41 found very low quality evidence that was insufficient to support or refute whether periodontal therapy can prevent the recurrence of CVD in the long term in patients with chronic periodontitis. No evidence on primary prevention was found.…”
Section: Clinical Conditions Affecting Cardiovascular Riskmentioning
confidence: 99%
“…[43][44][45] However, a recent Cochrane systematic review concluded that there was insufficient evidence to determine the effect of periodontal treatment on ACVD risk in individuals with chronic periodontitis. 46 Interestingly, two consensus reports on the subject were issued…”
Section: Discussionmentioning
confidence: 99%